What Sort of Collective Afterlife Matters and How. - Blumenthal-Barby, J. (Philosophia, 2016)
In Death and the Afterlife, Samuel Scheffler argues that the assumption of a 'collective afterlife' (i.e., the assumption that the human race and humanity lives on after our own individual deaths) plays an essential role in us valuing much of what we do. If a collective afterlife did not exist, our value structures would be radically different according to Scheffler. We would cease to value much of what we do. In Part I of the paper, I argue that there is something to Scheffler's afterlife conjecture, but that Scheffler has misplaced the mattering of a collective afterlife. Its significance lies not in the realm of axiology but more importantly in coming to terms with the fact of death and in viewing our lives as having meaning. In Part II of the paper, I outline three views on the sort of collective afterlife that matters and argue in favor of the view that it must involve creatures that recognize our existence, reasons, values, and contributions ('The Recognition Thesis') and the view that it must involve creatures that value similar things to us ('The Valuers Like Us Thesis')-but argue against the view that it necessarily be a human collective afterlife ('The Human Form Thesis').